Broad and durable antibody response after vaccination with inactivated SARS-CoV-2 in individuals with a history of 2003 SARS-CoV infection. Issue 1 (31st December 2022) - Liang, Huang; Zheng, Peiyan; Wang, Qian; Deng, Yijun; Liang, Dan; Yi, Haisu; Cheng, Yuanyi; Zhao, Xinwei; Ma, Jing; Yang, Yidong; Hu, Peiyu; Zheng, Pingqian; et al.
ABSTRACT: In vaccinees who were infected with SARS-CoV in 2003, we observed greater antibody responses against spike and nucleoprotein of both SARS-CoV-2 and SARS-CoV after a single dosage of inactivated SARS-CoV-2 vaccine. After receiving the second vaccination, antibodies against RBD of SARS-CoV-2 Wuhan, Beta, Delta, and recently emerged Omicron are significantly higher in SARS-CoV experienced vaccinees than in SARS-CoV naïve vaccinees. Neutralizing activities measured by authentic viruses and pseudoviruses of SARS-CoV, SARS-CoV-2 Wuhan, Beta, and Delta are greater in SARS-CoV experienced vaccinees. In contrast, only weak neutralizing activities against SARS-CoV-2 and variants were detected in SARS-CoV naïve vaccinees. By 6 months after the second vaccination, neutralizing activities were maintained at a relatively higher level in SARS-CoV experienced vaccinees but were undetectable in SARS-CoV naïve vaccinees. These findings suggested a great possibility of developing a universal vaccine by heterologous vaccination using spike antigens from different SARS-related coronaviruses.